Analisis Pengetahuan Dan Kepatuhan Pengobatan Pasien Diabetes Melitus Tipe 2 Di Puskesmas Kedungmundu Semarang - Rizky Budi Santoso; Nadya Putri Arissanti; Anak Agung Pradnya Paramitha Vidiani; Anisa Devi Kharisma; Anisa Nova Puspitaningrum (Fakultas Farmasi Universitas Tjut Nyak Dhien, 2026)
Type 2 Diabetes Mellitus is a chronic disease caused by metabolic disorders characterized by hyperglycemia due to impaired insulin secretion or action. Long-term management is required to prevent complications, making patient adherence to treatment essential. Patients’ knowledge of their disease significantly influences their attitudes and behaviors in undergoing therapy. This study aims to examine the relationship between knowledge levels and medication adherence among patients with Type 2 Diabetes Mellitus at Kedungmundu Public Health Center, Semarang. This research employed an analytical observational design with a cross-sectional approach conducted from March to June 2025. A total of 225 respondents were selected randomly using a simple random sampling method. The instruments used were the DKQ-24 questionnaire to assess knowledge and the Proportional Measurement of Adherence (ProMAS) questionnaire to evaluate medication adherence. Data were analyzed using Spearman's rank correlation test. The results showed that most respondents had a high level of knowledge (60.0%) and a high level of adherence (49.8%). Statistical analysis using the Spearman test revealed a significant relationship between knowledge and medication adherence (r = 0.536, p < 0.001). The higher the patients’ knowledge level, the higher their adherence to treatment. In conclusion, patients’ knowledge plays a crucial role in enhancing medication adherence among individuals with Type 2 Diabetes Mellitus. Therefore, structured health education should be emphasized as an effective strategy to improve disease management and patient outcomes.